Is there a need for antibiotic cover in clean surgery like laparoscopic cholecystectomy: a prospective study - Pai, Vishwanath; Aboosalih, Sana; Sundaram, S. N. Saravana; Abraham, Ann Rhoda; Prabhu, K. R. Manoj (International Surgery Journal, 2020)
Background: Even with a low post-operative infection complication rate in elective laparoscopic cholecystectomy (LC), most surgeons use prophylactic antibiotics out of habit. This prospective study was done to analyze the need for such prophylaxis in cases of elective LC. Methods: 135 successive patients undergoing elective LC were included in the study. Patients were randomized into 3 groups. Group A (n=45) cases received 3 doses of injection ceftriaxone in the post op period, group B (n=48) cases received a single dose of injection ceftriaxone at the time of induction of anesthesia, and group C (n=42) cases did not receive any antibiotic pre or post operatively. Post-operative infectious complications between three groups were compared. Results: There was no significant difference in surgical site infection rates between the groups for variables such as age, sex, body mass index, duration of symptoms, duration of surgery and hospital stay. Intraoperative spillage of bile [6.7% (A): 4.6% (B): 5.2% (C)] did not increase infectious complications. Conclusions: Routine use of prophylactic antibiotic in a clean, uncomplicated cases of laparoscopic cholecystectomy is not required. One dose of ceftriaxone at the time of induction or 3 doses of injection ceftriaxone post operatively following elective LC even in the urban Indian setting should be abandoned as it neither reduces the rate of surgical site infection but also contributes to adverse reactions, drug resistance, and unnecessary financial burden.